ALTERAÇÕES DA COMPOSIÇÃO QUÍMICA EM AVEIA PELO EFEITO DE CULTIVAR E LOCAIS DE CULTIVO - Silva, Jose A. G. d.; Crestani, Maraisa; Gutkoski, Luis C.; Fernandes, Sandra B. V.; Berto, Jorge L.; Carbonera, Roberto; Kruger, Cleusa A. M. B.; Camacho, Dagmar G.; Uhde, Leonir T.; Quadros, Valmir J. d.; et al. (Salão do Conhecimento, 2013)
Resumo